PEREMPUAN BERPELUH YANG TAK MENGELUH: STUDI TENTANG PEREMPUAN PEDAGANG SAYUR DI PASAR BATURITI, TABANAN, BALI - Ni Made Wiasti (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2011)
Trade business has become an important attraction to women because it is appropriatewith their physical ability and skill in bargaining activity as an essential element intrading.The involvement of women in trade business offers several advantages. Among others,they can earn their own income so they have contribution to the household economy.Women traders are also able to meet their social obligations as members of villagecommunities such as by giving donation during religious ceremonies and customaryrelatedactivities. In the pattern of decision making, they also gain autonomy within thehousehold to decide the daily household interests as well as to show off their veryimportant role in the household economy. Socially and culturally, women traders alsoearn a place in society as well as find a new status and network of relationships to otherpeople who are not known before. As a result, they can improve their knowledge andbroaden their perspective.